Tesis doctoral: Smart Tourism Destinations: A Demand-based Approach for Improving Local Tourism Management - Francisco Femenia Serra (Boletín de la Asociación de Geógrafos Españoles)
Femenia Serra, Francisco. Smart Tourism Destinations: A Demand-based Approach for Improving Local Tourism Management. Universidad de Alicante (España), diciembre de 2019. Director: Dr. Josep A. Ivars Baidal.